Can the World Cut Poverty in Half? How Policy Reform and Effective Aid Can Meet International Development Goals. - Collier, P; Dollar, D (2001)
Poverty in the developing world will decline by about one-half by 2015 if the trends of the 1990s persist. Most of this poverty reduction will occur in Asia, however, while poverty will decline only slightly in Africa. Effective aid could make a contribution to greater poverty reduction in lagging regions. Even more potent would be significant policy reform in these countries. We develop a model of efficient aid in which flows respond to policy improvements that create a better environment for poverty reduction and effective aid. We investigate scenarios of policy reform and efficient aid that point the way to how the world can cut poverty in half in every major region.